2020
DOI: 10.15388/ekon.2019.2.6
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of External and Internal Factors on Strategic Management of Innovation Processes at Company Level

Abstract: The impact of external and internal factors on organization of operation at company level is studied. The necessity for implementing strategic management of innovation processes at company level is substantiated. The structural interactions of external and internal factors on the organization of company operation are determined; a classification of factors of external and internal environment in the context of strategic management of innovation processes at company level is constructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This means that innovation is the driving force of the economy, a source of enterprise competitiveness and an opportunity to improve the living conditions of the society. The similar view is held by Shatilo (2019), who argued that an important factor of the company advancement is strategic management of innovation process. R&D can promote growth in total factor productivity (TFP) by helping to absorb new technologies embodied in foreign direct investment (FDI) and foreign trade (Shen et al, 2019).…”
Section: The Essence and Economic Significance Of Research And Develo...mentioning
confidence: 58%
“…This means that innovation is the driving force of the economy, a source of enterprise competitiveness and an opportunity to improve the living conditions of the society. The similar view is held by Shatilo (2019), who argued that an important factor of the company advancement is strategic management of innovation process. R&D can promote growth in total factor productivity (TFP) by helping to absorb new technologies embodied in foreign direct investment (FDI) and foreign trade (Shen et al, 2019).…”
Section: The Essence and Economic Significance Of Research And Develo...mentioning
confidence: 58%
“…They have impacts on several aspects of enterprise operation and the management of innovation. Those components allow us to determine its competitive position, the position that the enterprises occupy in the industries, and a special market integration, according to the company's performance compared to other enterprises [40,41] From this view, the strengths and weaknesses are judged as internal factors (priorities), while opportunities and threats are external factors [42][43][44]. It is clearly observed that the SWOT technique provides a descriptive investigation and assessment to analyze the quantifiable selected components [45][46][47].…”
Section: Evaluation Scheme: An Extensive Understanding Of Ahp and Swo...mentioning
confidence: 99%
“…the variables that affect the performance of construction firms. Even though the construction industry has a good understanding of performance management, the nature of environmental elements' impact as intangible or tangible resources on total performance is still uncertain [18,19]. These external influences can put pressure on businesses to detect their advantages and shortcomings, as well as fashion processes for recognising and adapting to pertinent business opportunities and changing corporate settings for either the reduction or elimination of economic risks towards performance enhancement.…”
Section: Construction Firm Performance Outcomesmentioning
confidence: 99%